Quarry Dust and Kenaf Core: An Ideal Waste By-Product as Alternative Fine Aggregate for Producing Lightweight Cement Brick - Kamaruddin, Khairol; Ismail, Lokman Hakim; Zakaria, Mohd Azuan (International Journal of Sustainable Construction Engineering and Technology, 2025)
In response to growing environmental concerns and a scarcity of natural resources, finding sustainable alternatives to sand cement bricks has become a critical challenge. This study explores the feasibility of using quarry dust (QD) and kenaf core (KC) as eco-friendly replacements for conventional fine aggregates to produce lightweight cement bricks. Eight mixed proportions of bricks were manually prepared using a cement-to-fine aggregate ratio of 1:6 (volume ratio) and a water-to-cement ratio of 0.6, with conventional sand cement bricks as the baseline. The bricks were tested for density, compressive strength, water absorption, initial absorption rate, and thermal conductivity. The results revealed that QD significantly enhances compressive strength and density, achieving values of up to 35.14 MPa and 2,076 kg/m³, representing a 70.6% improvement in strength compared to conventional sand cement bricks, which have a compressive strength of 20.6 MPa. Conversely, KC demonstrated its ability to reduce brick weight and thermal conductivity, with values as low as 527 kg/m³ and 0.12 W/mK, respectively. These findings underscore the trade-off between strength and thermal performance when using KC. The study identifies an optimal mix of 25% KC and 75% QD, producing lightweight, non-loadbearing bricks with a density of 1,576 kg/m³, compressive strength of 5.34 MPa, water absorption of 15.6%, initial absorption rate of 12 g/min./193.55cm², and thermal conductivity of 0.51 W/mK. While KC’s incorporation delayed setting times and increased brittleness, adhesives or additives are recommended to mitigate these challenges and enhance practical applications. This research contributes to the advancement of sustainable construction by providing a viable pathway for developing eco-friendly, lightweight bricks that meet industry standards for non-loadbearing applications while addressing critical environmental and resource challenges.